A Linguistic Study of Euphemism and Dysphemism in Lois Lowry’s the Giver and George Orwell’s Animal Farm - Duriat, Fajar; Said, Mashadi; Supadi, Supadi (INFERENCE: Journal of English Language Teaching, 2024)
This study investigates the use of euphemisms and dysphemisms in Lois Lowry’s The Giver and George Orwell’s Animal Farm within the framework of Politeness Theory, focusing on how these linguistic strategies influence societal norms and individual roles. This research employs a descriptive qualitative method, which focuses on the detailed analysis and interpretation of textual data. The results demonstrate that euphemisms align with negative politeness and off record strategies to obscure unpleasant truths, while dysphemisms correspond with bald on record strategies to directly attack and discredit. Both novels strategically employ euphemisms to soften harsh realities and maintain societal control, while dysphemisms are used to stigmatize opposition and reinforce authority. The implication of this study is that it highlights how language shapes reality, enabling students to critically analyze linguistic manipulation. Moreover, by examining euphemisms and dysphemisms in The Giver and Animal Farm, students gain insights into control, power, and oppression, while exploring the connection between language and societal critique in dystopian literature.